As complexas assinaturas genéticas dos casamentos não casuais e da dinâmica de miscigenação no cromossomo x dos brasileiros - Hanaisa de Plá e Sant’Anna (2016)
The Brazilian history is marked by a complex dynamic of admixture, with the occurrence of sex bias with African and Native American female bias and European male bias, and also by an ancestrally related positive assortative mating. To investigate the effects of these non-random mating in the genetic structure of Brazilians, we analyzed 37,457 Single Nucleotide Polymorphism (SNPs) on X chromosome of 5,823 individuals from three cohorts in Brazil with different admixture dynamics: Salvador (Northeast), Bambuí (Southeast) and Pelotas (South). Our results show the potential of the X chromosome to demonstrate patterns of mating in Latinos. First, we observed an excess of African and Native American contributions in genetic diversity of the X chromosome compared to the autosomes, which supports the occurrence of sex bias. Second, we noted that non-random mating leads to deviations in the genotype frequencies predicted by Hardy-Weinberg resulting in differences in allelic frequencies between male and female mainly on X chromosome SNPs with high genetic differentiation between Europeans and Africans. These highly differentiated SNPs also show an excess of homozygosity, which supports the existence of preferential mating between Brazilians with the same ethnic background. Besides these signatures of non-random mating on the X chromosome of Brazilians, we also elucidated further aspects of the dynamics of admixture in Brazil. We analyze the distribution of Chromosome Segments of Continuous Specific Ancestry (CSSA) of the X chromosome and we show the older contribution of Native Americans to the Brazilian genomic diversity, the recent European immigration in the southeast and south of the country, and the newest contribution of Africans in the northeast. Thus, this study contributes to the understanding of the demographic events that have shaped the complex genetic structure of the Brazilian population.